El uso de la enzima transglutaminasa en productos cárnicos - Benavides Mendoza, Karen Lizeth (2018)
The present research work has as main objective is the extraction and the analysis of data in order to determine how useful and beneficial of the enzyme transglutaminase, and in this way to lessen the forfeiture of meat products within the Food and Beverage industry. By using the enzyme transglutaminase, in the food industry or restoration, new and interesting restructured meat products from pieces or leftovers of meat may be produced with the aim of avoiding wastes inside the food industry and hence to obtain reconstituted, optimal, harmless and attractive food in front of the consumer.